Five new species of Microcerella Macquart, 1851 (Diptera: Sarcophagidae) from the Andean Region - Rodrigues dos Santos, Josenilson (2025)
Five new species of Microcerella Macquart, 1851 are described from the Andean Region: one from Argentina, Microcerella obscura sp. nov., two from Chile, Microcerella desertum sp. nov. and Microcerella grinteri sp. nov., one from Ecuador, Microcerella hyperbole sp. nov., and one from Peru,Microcerella jimi sp. nov. The male morphology is documented with photographs and illustrations,including details of the terminalia for all new species. New morphological structures in the phallus areobserved for these new species of Microcerella, the median and lateral processes.